The making of Minecraft - Zeiger, Jennifer (Ann Arbor, Michigan : Cherry Lake Publishing, 2017)
With more than 100 million players around the world, Minecraft is one of the most popular video games of all time. Its unique design encourages players to use their creativity and problem solving skills to build entire worlds from scratch. In this book, readers will discover how the game began as the hobby project of a single independent game designer and grew to become a worldwide phenomenon.
Includes bibliographical references (page 31) and index.
6.6
5-8
Keywords: Minecraft (Game) -- Juvenile literature; Video games -- Juvenile literature; Minecraft (Game); Video games; Computer games